Strategi Pengelolaan Pantai Banyu Tibo Berbasis Ekowisata Di Kabupaten Pacitan Jawa Timur - Nur Rohman; Dwiyono Rudi Susanto; Amin Kiswantoro (STIE Pariwisata API Yogyakarta, 2020)
Banyu Tibo Beach is one of the beaches in Pacitan Regency. This beach has uniqueness of a waterfall overlooking the beach. This research aims to find out the right management strategy for Banyu Tibo Beach to be ecotourism. This research method used a descriptive qualitative analysis method. Data collection techniques were carried out by distributing questionnaires with non-probability sampling techniques to 100 respondents in Banyu Tibo Beach by taking using incidental sampling techniques. The data obtained is then processed using SWOT analysis to determine the strengths, weaknesses, opportunities and threats that exist in Banyu Tibo Beach. From the data processing, obtained the right strategies to manage the Banyu Tibo Beach in ecotourism, namely by providing or adding infrastructure to support ecotourism-based tourism activities, making or adding environmentally friendly tourism products, conducting training on ecotourism for human resources managing Banyu Tibo Beach, in collaboration with all parties to play an active role in the implementation of sustainable tourism activities.